A Case Study on Internet Access Conditions of Boarding School Students During the Home-Based Learning and Teaching Sessions (Hbl) According to the Area of Residence - Muhammad Iqbal Sofian; Muhammad Harith Hasif; Nor Raihan; Noor Farina Febra (Kolej Genius Insan, Universiti Sains Islam Malaysia, 2024)
2nd Insan Junior Researchers International Conference 2021 (iJURECON 2021) “STREAM for a Better Life” 15-17th October 2021 Organized By :Kolej GENIUS Insan of Universiti Sains Islam Malaysia